Nutritional Status and Eating Behaviors among Adolescents of Some Intermediate Schools in Jeddah - Thanaa A. Alkoly,; Asmaa M. AbdAllah,; A. K. Alghamidi, (Journal of King Abdulaziz University: Medical Sciences, 2023)
This study aims to evaluate healthy food habits and nutritional knowledge amongst adolescents; the impact of the previous factors on their nutritional status and, the influence of food availability and television viewing habits on their eating behaviors. A cross-sectional descriptive study, including 140 Saudi students, male (70) and female (70) from intermediate schools in Jeddah, Kingdom of Saudi Arabia. Validated questionnaires were used to measure the family environment, socioeconomic status, dietary habits, nutritional knowledge, hygienic habits, health habits, and anthropometric measurement. Daily dietary intake was conducted using 24 hours recall method. Computer software package was used for diet analysis and compared by RDA. SPSS computer software ver.10 was used in data analysis. The main age was 14.8 ± 0.7 for male and female 14.2 ± 0.9. Fruit intake in boys was 67.2% and girls 50%. Sixty percent of females and 61.4% of males skipped daily meals. Availability of healthy food at home was 61.9% for males and 48.6% females. Sixty-seven point one percent of both genders have 2 meals/day; however, 88.6% of males and 84.3% of females have 3 meals/day. The mean intake of protein for females was 147.3 and 130.8 for males. The mean food intake of studied subjects in comparison to the recommended daily dietary allowances was high. This study shows that eating behaviors for intermediate schools still require development.